LABOR SHARE AND GROWTH IN THE LONG RUN. (27th October 2020) - Charpe, Matthieu; Bridji, Slim; Mcadam, Peter
Abstract : This paper establishes some stylized facts of the long-run relationship between growth and labor shares using historical data for the USA (1898–2010), the United Kingdom (1856–2010), and France (1896–2010). Performing individual country time–frequency analysis, we demonstrate the existence of long-term cycles in labor share of 30–50 years explaining a major part of the variance in the data. Further, the impact of labor share on growth changes sign with the frequency considered from negative at high frequencies to positive at low frequencies. Finally, the positive coefficient associated with the labor share at low frequencies increases over time.